Pode a mulher falar? Discursos de mulheres vítimas de abusos sexuais/estupro - Leite, Joana Rodrigues Moreira (2020)
Sexual abuse / rape of women has been a social issue which deserves attention once this violence has produced its effects on the bodies of victims, especially psychological problems. Thus, I aimed at analyzing the discursive formations (excerpts) produced by six women living in a city in the interior of the State of Mato Grosso, who had suffered sexual abuse and / or rape. The intention was to verify which discourses were constituted around the practices / relationships of knowledge and power between the female and male genders; to examine which statements are produced by the victims about sexual abuse / rape and discuss the effects of sexual violence on the bodies of those women. Therefore, three questions organize the problematization: 1) How were the discursive formations of the victims / subjects of research being organized around the rape subject matter? 2) Which discourses prevailed in the statements highlighted in the discursive formations based on the power and knowledge relationships between the female and male genders? 3) What are the effects of rape on the lives of victims of this violence? The qualitative-interpretative methodology, in the perspective of Flick (2009), intertwined with the discourse analysis of Foucault (2008) was used. The data were generated through semi-structured interviews conducted with the six participants. Seven recurring themes emerged after the transcription and observation of the data, which are discussed in this thesis: difficulty in talking about rape; proximity to the abuser / rapist; definition of rape; fear, judgment, guilt and silencing the victim; reporting the rape; current consequences of rape. In consideration of such themes, the theoretical basis with emphasis on Applied Linguistics was chosen to dialogue with these themes. The female authors and male authors are from several areas of Social and Human Sciences, such as: Gayatri Chakravorty SPIVAK (2010); Michelle PERROT (2017); Heleieth SAFFIOTI (2015); Débora Carvalho FIGUEIREDO (2000; 2002; 2014); Fernanda MUSSALIM (2003); Renata Floriano SOUSA (2017); Daniella Georges COULOURIS (2010); Arielle Sagrillo SCARPATI (2013); Sueann CAULFIELD (2000); Susan BROWNMILLER (1976); Lia Zanotta MACHADO (1998); VIGARELLO (1998); FOUCAULT (1979; 1984; 1987; 2008); SCOTT (2011), among others.The problematization of the research points at the difficulty rape victims demonstrate to talk about the subject; the rapist tends to be a family person or friend; violence happens at home; the addressed rapes, mostly, occurred in childhood or adolescence; in adulthood, they also involved acquaintances, such as friends or husbands. In the discourses of the participants, linguistic elements emerged around: morality, religiosity, family silence, naturalization of violence, absence of denunciation, forgiveness to the abuser, family chauvinism, submission, guilt and shame. In this scope of violence and abuse, the effects of rape have more psychological effects than physical consequences on the victims’ bodies.